The effects of using mobile device in learning English language: a comparison through experimental study - Hamzah, Mohd Sahandri Gani; Ali, Zuraina; Abdullah, Saifuddin Kumar; Abdullah, Nurul Farhana (2010)
Mobile learning in the current meaning of the term has developed since about 2002. It grows out of a community of practitioners and researchers drawn from education and technology. The essence of mobile English learning mode is to make full use of the ubiquitous English language environment created by mobile devices, and help students turn English learning activities into rich and colourful one. In this paper, a series of mobile device-based English activities are designed, and experimental research is conducted between mobile and conventional learning. The study employs a non random sampling involving 60 students from Bachelor in Information and Communication Technology (ICT) course semester six. The collection of data conducted for a period of seven weeks. In this period pre-test (Comprehension test) was implemented to determine the same level of students’ performances. Whereas post-test was conducted for, speech presentation and collaborative Identification and the data was analysis by using independent sample t-test and gain scores differences in post-test 1 and post-test 2) to determine the effectiveness between treatment and control group. The research conducted to answer 8 null hypotheses in the study and the result shows 5 null hypotheses accepted and 3 null hypotheses rejected. By conducting experimental research, we review the feasibility of the model and the effectiveness of mobile learning. Research has shown that this new learning model (mobile) has positive effects in promoting University Putra Malaysia students’ interest towards English learning, as well as their mastery of knowledge and their development of collaborative learning skills. In addition, boys and girls shows there are no significant differences in speech presentation and collaborative identification in both groups.